IMPROVEMENT OF NOVEL REVIEW TEXT SKILLS THROUGHT THINK TALK WRITE MODEL IN SMP NEGERI 3 RAMBAH (PENINGKATAN KETERAMPILAN MENULIS TEKS ULASAN NOVEL MELALUI MODEL THINK TALK WRITE DI SMP NEGERI 3 RAMBAH) - Rita Arianti (Universitas PGRI Sumatera Barat, 2020)
This research was conducted because of the low activity and student learning outcomes in writing review texts. This is due to the lack of creativity of students and teachers in supporting the achievement of learning goals.This study aims to describe the increase in activity and learning outcomes of writing novel text review skills through the Think Talk Write model on class VIII SMP Negeri 3 Rambah. This type of research is classroom action research. The method of this research is qualitative and quantitative methods. The research subjects were class VIII students totaling 26 people. The data analysis technique of this research is qualitative and quantitative techniques. The results of this study are (1) an increase in the quality of student activities from prasiklus by 36% (lack of quality), cycle I by 60% (quite high quality), cycle II at 76% (quality), cycle III by 94% (very high quality) , and (2) an increase in completeness of pre-cycle learning outcomes of 46.15% with an average value of 67.88, cycle I of 61.53% with an average value of 76.15, cycle II of 80, 76% with the average value of 80.65 in the third cycle was 96.15% with an average value of 85.04. Based on the results of the study it can be concluded that the application of the Think Talk Write model in writing novel review texts is able to improve the activity and learning outcomes of class VIII SMP Negeri 3 Rambah.